(untitled) (Fiep Bulletin - online, 2014)
This paper aims to show that initiation of sport is a way to stimulate and improve the sport, with proper guidance of teachers, so that practitioners hold your focus on improving your sports performance, and noted the importance of parental involvement along children and adolescents. Given that a project was developed by the University of Rio Grande in partnership with the city of Duque de Caxias, called PRODUC - Initiation Sports, who have in order to develop physical skills, cognitive, affective, social and moral young people between seven and fifteen years of both sexes. However, the method we have chosen for construction of the present study is the volleyball assuming that this sport reduces the rate of violence, to be collective and without body contact with the opponent. The aim was to bring a discussion about sports initiation within the PRODUC - Initiation Sports, with emphasis on volleyball. The methodology chosen for the study was a qualitative, of bibliographical. The results imply that the discussion PRODUC is suited to being presented with the literature regarding age of initiation, body and cognitive aspect. But while volleyball is a sport without direct physical contact, it was not possible to obtain direct data if there is any influence on violence. Research has shown that through sports initiation, with emphasis on volleyball, is possible through the practice help reduce violence and promote the development of cognitive, motor, social and emotional child and adolescent.